Synthesis 1,1-Dibutoxybutane from Single Reagent of n-Butanol Using Cr/Activated Carbon Catalyst - Iip Izul Falah; Mokhammad Fajar Pradipta; Alvan Luthfi Rinaldi; Wega Trisunaryanti (Indonesian Journal of Chemistry, 2020)
Synthesis of 1,1-dibutoxybutane from the single reagent of n-butanol using Cr/Activated Carbon (Cr/AC) as a catalyst has been done. The aims of this research were to evaluate the effect of temperature, amount of catalyst, and alcohol flow rate towards the yield of 1,1-dibutoxybutane. Activated carbon (AC) was prepared by activating coconut shell carbon at 650 °C in the atmosphere of H2 at a flow rate of 15 mL/min for 4 h, and then it was washed using acetone in a Soxhlet for 15 rounds, washed 3 times by 1.0 M HCl, and finally, it was sieved at 60–80 mesh. Metal content was analyzed using atomic absorption spectroscopy (AAS) of Na, Ca, and Fe. The AC was impregnated with Cr(VI) solution and reduced with H2 at 650 °C. The acidity of Cr/AC catalyst was determined by the adsorption of ammonia vapor. Optimization of n-butanol conversion to 1,1-dibutoxybutane using Cr/AC catalyst was conducted in an oven using variations of temperature of 450, 500, and 550 °C, catalyst amount of 5, 10, and 15 g, under an alcohol flow rate of 0.10, 0.50, and 0.90 mL/min. The conversions of 1,1-dibutoxybutane were analyzed by GC-MS and 1H-NMR. The results showed that after washing by acetone and 1.0 M HCl, the content of metals in the AC was significantly decreased. The AC and Cr/AC showed acidity of 2.49 and 8.27 mmol/g, respectively. The highest product of 1,1-dibutoxybutane (53.42%) was reached at 450 °C using 5 g catalyst of Cr/AC under the alcohol flow rate of 0.10 mL/min.